Selling tourist destinations : geography for travel professionals - Mancini, Marc (Australia : Cengage Learning Asia Pte Ltd, 2009)
"Selling Destinations offers a fresh approach to teaching and learning travel geography. Following an introductory overview, the text is divided into six parts, covering major travel destinations around the world. The most popular locations visited by Americans receive detailed treatment in chapters of their own. Secondary destinations merit several pages or paragraphs in special potpourri chapters specific to each region. This text makes the study of geography academically rigorous and fun. It uses magazine-style prose, two-color highlighting, lists, headings, subheadings, graphs, tables, photos, case studies and application activities to teach, clarify and reinforce the information. More than 300 visual elements enliven the material presented. They are attractively presented in the form of maps; FYI, Travel Trivia and Margin Notes boxes; climate charts; and grid boxes identifying the types of people who are attracted to major destinations. These essential elements help the student retain much more information than they would with a traditional textbook. The sales-geography philosophy is supported by essential information that will help travelers make the most of their experiences. It fully addresses such topics as travel to the destination, local modes of transportation, trip highlights and day trips, lodging options and allied destinations. Sales strategies focus on extra services that yield extra income for almost all travel professionals. Each chapter closes with a map activity testing knowledge of geographic locations and their attractions, a case study to apply the knowledge learned to hypothetical travelers and a creative activity that challenges the student to find an innovative solution to a hypothetical situation. These activities lend themselves well to in-class group discussions." -- Amazon.com viewed February 5, 2021.
Part I. Basic Ingredients: Geography and How to Sell It -- Part II. North America: Charm of the Familiar -- 1. New England: The Cradle of Charm -- 2. New York and New Jersey: Broadway and Boardwalk -- 3. Pennsylvania, Maryland, Virginia and Washington, D.C.: The Mid-Atlantic Medley -- 4. Florida: Where the Mouse Roars -- 5. California and Arizona: Glamour and Grandeur -- 6. Canada and Alaska: The Great White North -- 7. Hawaii: Paradise Found -- 8. North American Potpourri (East) -- 9. North American Potpourri (West) -- Part III. Latin America and the Caribbean: Rhythms of Culture -- 10. Mexico: Tropical Fiesta -- 11. The Caribbean: A Sea of Nations -- 12. Brazil: Where Everything Sizzles -- 13. Latin American Potpourri -- Part IV. Europe: Continental Flair -- 14. Great Britain and Ireland: Foreign, Yet Familiar -- 15. France: The Movable Feast -- 16. Italy: Pisa and Pizza -- 17. Spain and Portugal: Everything Under the Sun -- 18. Germany: Romantic Roads -- 19. Greece and Turkey: An Odyssey of Culture -- 20. European Potpourri -- Part V. Africa and the Middle East: Savannahs and Sand -- 21. Egypt: Riddles in the Sand -- 22. Israel, Palestine and Jordan: The Holy Lands -- 23. Kenya and Tanzania: The Lion Sleeps Tonight -- 24. African and Middle EasternPotpourri -- Part VI. Asia and the Pacific: Rim of Mystery -- 25. Australia and New Zealand: Where Things are Jumping -- 26. The Pacific: Fantasy Islands -- 27. Japan: Pearl of the Orient -- 28. Singapore and Thailand: Crossroads of Asia -- 29. China: Of Red and Gold -- 30. Asia and the Pacific Potpourri -- Appendix A. Average Length of Stay -- Leisure Travelers -- Appendix B. Research Resources -- Appendix C. Destination-Related Feature Films.
Includes bibliographical references and index.
Keywords: TOURISM